The environmentalisation of the school curriculum: Brief review of a hazardous history - González Gaudiano, Edgar J. (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The paper discusses the process of curricular environmentalisation under the conventional curriculum depletion suffered in the last two decades. It argues that while the incorporation of the environmental dimension into the formal education system could have led to a revitalization of school processes given their intrinsic articulatory characteristics, the loss of the school curriculum heuristic capabilities constrained environmental education to a series of discrete contents and a proposal for transversalisation that was never consummated in fact. The advent of education for sustainable development and emergent complex issues such as climate change, follow the same hackneyed path of transformations minimalist least disturb the status quo of the disciplines, as well as the social order that is transmitted through the curricular content and atavist rituals that take place in the classroom, now mediated by information technologies and communication.